DOT1L affects colorectal carcinogenesis via altering T cell subsets and oncogenic pathway. (31st December 2022) - Sun, Danfeng; Wang, Weichao; Guo, Fangfang; Pitter, Michael R.; Du, Wan; Wei, Shuang; Grove, Sara; Vatan, Linda; Chen, Yingxuan; Kryczek, Ilona; Fearon, Eric R.; Fang, Jing-Yuan; et al.
ABSTRACT: Chronic inflammation and oncogenic pathway activation are key-contributing factors in colorectal cancer pathogenesis. However, colorectal intrinsic mechanisms linking these two factors in cancer development are poorly defined. Here, we show that intestinal epithelial cell (IEC)-specific deletion of Dot1l histone methyltransferase ( Dot1l ΔIEC ) reduced H3K79 dimethylation (H3K79me2) in IECs and inhibited intestinal tumor formation in Apc Min - and AOM-DSS-induced colorectal cancer models. IEC- Dot1l abrogation was accompanied by alleviative colorectal inflammation and reduced Wnt/β-catenin signaling activation. Mechanistically, Dot1l deficiency resulted in an increase in Foxp3 + RORϒ + regulatory T (Treg) cells and a decrease in inflammatory Th17 and Th22 cells, thereby reducing local inflammation in the intestinal tumor microenvironment. Furthermore, Dot1l deficiency caused a reduction of H3K79me2 occupancies in the promoters of the Wnt/β-catenin signaling genes, thereby diminishing Wnt/β-catenin oncogenic signaling pathway activation in colorectal cancer cells. Clinically, high levels of tumor H3K79me2 were detected in patients with colorectal carcinomas as compared to adenomas, and negatively correlated with RORϒ + FOXP3 + Treg cells. Altogether, we conclude that DOT1L is an intrinsic molecular node connecting chronic immune activation and oncogenic signaling pathways in colorectal cancer. Our work suggests that targeting the DOT1L pathway may control colorectal carcinogenesis. Significance : IEC-intrinsic DOT1L controls T cell subset balance and key oncogenic pathway activation, impacting colorectal carcinogenesis.